The effects of background risk on behavioural lateralization in a coral reef fish. (23rd June 2015) - Ferrari, Maud C.O.; McCormick, Mark I.; Allan, Bridie J. M.; Choi, Rebecca B.; Ramasamy, Ryan A.; Chivers, Douglas P.
Summary: Behavioural lateralization – the preferential use of one side of the body or either of the bilateral organs or limbs – has been well documented in many species, in a number of contexts. While the benefits reported are numerous, existing latent variability in the degree of lateralization within and across populations, species and taxa indicates that existing costs may modulate its expression. Few studies have reported changes in the degree of lateralization at the individual level, in response to long‐term changes in environmental conditions, but not in response to short‐term changes in environmental conditions. Predation is highly variable both temporally and spatially and hence is a good candidate for testing lateralization effects based on short‐term changes in environmental conditions. Here, we tested the hypothesis that the degree of behavioural lateralization changes following short‐term exposure to different levels of risk. We tested whether wild‐caught juvenile damselfish exposed to a high or low background level of risk for 4 days would subsequently differ in their turning bias, a trait that has been linked to predator escape behaviour in fishes. We found that 4 days is enough to induce a difference in the absolute lateralization scores of the fish, with high‐risk fish being more strongly lateralized than low‐risk fish. Practically, this difference stemmed from decreasing lateralization scores for newly recruiting coral reef fishes that were kept in low‐risk environments, with the concurrent maintenance of higher lateralization scores for fish maintained under high‐risk conditions. Fish from the high‐risk background had higher survival than those from the low‐risk background upon release into mesocosms containing reef predators. Our study highlights how early exposure to differential predation risk affects the degree of behavioural lateralization. Given the profound effects of lateralization on many aspects of an animal's life from its ability to discriminate conspecifics to how it forages and interacts during agonistic interactions, predation risk may be a key driver of animal development. Abstract : Lay Summary